PENGUNGKAPAN MODAL INTELEKTUAL PERGURUAN TINGGI VOKASI DI INDONESIA BERDASARKAN INSTRUMEN AKREDITASI PROGRAM STUDI (IAPS) 4.0 - Lilik Intan Herawati; Ihyaul Ulum; Ahmad Juanda (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2020)
The purpose of this research is to identify and provide a high level description of intellectual capital disclosure of vocational colleges in Indonesia based on the Accreditation Instrument of Study Program (IAPS) 4.0. Six ways numerical coding system of content analysis was used to analyze the data. The results indicate that IC disclosure patterns chosen by vovational colleges in Indonesia are mostly in the form of pictures / graphics and narratives. However, the number of undisclosed IC items was very dominant (47.4%).